Development of IoT-based Scheduled and Efficient Feeding System For Broiler Chicken - Gerin Sonia Yuki Lumban Tobing; Purba Daru Kusuma (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
This research aims to develop a scheduled, efficient, and optimal Internet of Things (IoT)-based feeding system for broiler chickens. In an effort to improve efficiency and sustainability in poultry farming, a technology-based approach becomes crucial. Currently, the use of farm monitoring systems is generally conventional or manual, and human labor involvement incurs significant costs. In the era of Society 5.0, innovative solutions that leverage cutting-edge technology are needed to enhance productivity and sustainability in farming. This study adopts a prototype development method with sorting algorithms to develop an efficient and scheduled feeding system for broiler chickens. The system consists of automation devices capable of regulating chicken feed volumes and implementing regular scheduling. Furthermore, the system utilizes Internet of Things (IoT) technology, enabling remote control and real-time monitoring through an Android application. With this system in place, farmers can efficiently monitor and regulate chicken feeding without the need to be physically present at the farm location. Additionally, the use of sorting algorithms allows for the even distribution of feed, reducing waste and maximizing feed utilization. The development of this IoT-based feeding system for broiler chickens is expected to enhance efficiency and sustainability in poultry farming while making a positive contribution to meeting the future high demand for chicken meat.